Analisis Logical Fallacy terhadap Masalah Lingkungan dan Pengelolaan Sumber Daya Alam di Media Sosial - Ridho Darman (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
This study aims to identify and analyze the logical fallacies that arise in public conversations about environmental issues and natural resource management on Indonesian social media using a descriptive qualitative approach. Data were collected through scraping techniques using the Python programming language and subsequently analyzed using an informal logic framework to identify various forms of fallacious reasoning. The findings reveal the presence of multiple fallacies that substantially influence public understanding of causal relationships within environmental dynamics. These fallacies contribute to oversimplification, shifts in attention away from scientific evidence, and the emergence of distorted perceptions regarding structural factors in spatial planning and natural resource governance. This study contributes to environmental communication scholarship by emphasizing the importance of critical thinking literacy in improving the quality of public deliberation and supporting the formulation of evidence-based environmental policies.